2009
DOI: 10.1002/masy.200950701
|View full text |Cite
|
Sign up to set email alerts
|

Heterophase Polymerization as Synthetic Tool in Polymer Chemistry for Making Nanocomposites

Abstract: Summary: The paper considers various possibilities to produce inorganic -polymeric nanocomposites via aqueous heterophase polymerization. Special emphasis is placed on strategies to synthesize nanocomposite particles via joint nucleation or joint polymerization. The former strategy is used to make composite particles with CaCO 3 as inorganic component. The strategy of joint polymerization takes advantage from the condition that aqueous heterophase polymerization is a convenient possibility to synthesize amphip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It has been observed with advanced light scattering techniques that spontaneous emulsification of organic solvents, that do not swell nanoparticles, in water causes shell formation around the nanoparticles. [120] For example, formation of nanometer thick shells of oct-1-ene and hexane on polystyrene and silica nanoparticles has been proven. During emulsion polymerization, swelling and propagation takes place simultaneously.…”
mentioning
confidence: 99%
“…It has been observed with advanced light scattering techniques that spontaneous emulsification of organic solvents, that do not swell nanoparticles, in water causes shell formation around the nanoparticles. [120] For example, formation of nanometer thick shells of oct-1-ene and hexane on polystyrene and silica nanoparticles has been proven. During emulsion polymerization, swelling and propagation takes place simultaneously.…”
mentioning
confidence: 99%
“…This fact is a kind of trademark of the ceric ion redox initiation and is supportive for the successful synthesis of block copolymers via free radical polymerization as discussed in ref . The particular role of the chain length of the water‐soluble polymeric reductant and of the PNIPAM middle block on the polymerization process has been discussed in ref . Moreover, it has been convincingly experimentally proven by reaction calorimetry that radical formation with poly(ethylene glycol) as reductant takes place exclusively at the methylol end groups and not additionally along the polyether chain (see ref…”
Section: Resultsmentioning
confidence: 96%
“…On the contrary, hydrophilic polymers as reductant cause the formation of block copolymer particles with ordinary SSM. In other studies, we have shown that in order to get stable block copolymer latexes with poly(ethylene glycol) as reductant, its molecular weight must be higher than about 2000 g mol −1 …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This experiment is one of the few studies in the field of the characterisation of the ion distribution about such large particles [7]. A related observation concerncs the wetting of colloidal interfaces in an aqueous medium by oct-1-en [15].…”
Section: Epj Web Of Conferencesmentioning
confidence: 97%